Africa RISING-The Effect of Nutrition Management on the Performance of Local Chickens in Tanzania - International Livestock Research Institute (International Livestock Research Institute, 2015)
This proposal focuses on forages and feed as a key opportunity for driving sustainable intensification of crop livestock systems in Tanzania. In 2013-2014, the livestock component was divided into two work packages (i) Screening and integrating forages in systems and improved use of crop residues and (i) developing feeds for indigenous poultry from local feed resources. In 2014-2015, the two work packages have been merged into an integrated livestock feeds component (ILF) to enhance integration. This component is designed to have three sub components as follows: (i) The first sub component revolves around screening forages, testing them with farmers and integrating them into existing farming systems. (ii) The second sub component is enhanced integration of crop residues in smallholder farms through improved storage, processing and utilization for ruminants. (iii) The third sub component is concerned with improved management and feeding strategies with emphasis on utilization of local feed resources for indigenous poultry. To learn more about this dataset, please visit the ILRI Datasets Portal http://data.ilri.org/portal/dataset/africa-rising-the-effect-of-nutrition-management-on-the-performance-of-local-chickens-in-tanzania